Blood diamond [videorecording (DVD)] - Zwick, Edward; DiCaprio, Leonardo; Connelly, Jennifer; Hounsou, Djimon, 1964- (Warner Bros. Pictures : Distributed by Warner Home Video, 2007)
Set against the backdrop of civil war and chaos in 1990's Sierra Leone, Blood Diamond is the story of Danny Archer - an ex mercenary from Zimbabwe - and Solomon Vandy - a Mende fisherman. Both men are African, but their histories as different as any can be, until their fates become joined in a common quest to recover a rare pink diamond that can transform their lives. While in jail for smuggling, Archer learns that Solomon - who was taken from his family and forced to work in the diamond fields - has found and hidden the extraordinary rough stone. With the help of Maddy Bowen, an American journalist whose idealism is tempered by a deepening connection with Archer, the two men embark on a trek through rebel territory, a journey that could save Solomon's family and give Archer the second chance he thought he would never have.